Dicentrarchus labrax - Bariche, Michel; Fricke, Ronald (Zenodo, 2020)
Dicentrarchus labrax (Linnaeus 1758) —European seabass Taxonomy. First record from Lebanon as Labrax lupus , Cuv. by Gruvel (1931: 99); subsequently recorded as Dicentrarchus labrax (Linnaeus 1758) by George et al. (1964: 17); as Dicentrarchus labrax (Linnaeus) by Mouneimné (1977: 62); as Dicentrarchus labrax (Linnaeus 1758) by Mouneimné (2002: 130). Material in collection: AUBM and BMNH. Distribution. Western Baltic Sea, North Sea, Mediterranean Sea, Sea of Marmara, Black Sea, eastern Atlantic: Norway and Iceland south to Senegal; recorded as NIS from the Red Sea and the Gulf of Suez. Conservation. IUCN: Global (LC: 1 January 2008); Med. (NT: 16 November 2007). Capture and threats: FIT, HAB, Unknown. Occurrence: Common. Medium priority for conservation action. Dicentrarchus punctatus (Bloch 1792) —Spotted seabass Taxonomy. First record from Lebanon as Labrax punctatus , Brito-Capel. = Morone punctata Bloch. by Gruvel (1931: 99); subsequently recorded as Dicentrarchus punctatus (Bloch 1792) by George et al. (1964: 17); as Dicentrarchus punctatus (Bloch) by Mouneimné (1977: 62); as Dicentrarchus punctatus (Bloch 1792) by Mouneimné (2002: 131). Material in collection: AUBM and USNM. Distribution. Mediterranean Sea, eastern Atlantic: English Channel south to Senegal; recorded as NIS from the Red Sea. Conservation. IUCN: Global (LC: 14 July 2014); Med. (LC: 16 November 2007). Capture and threats: Unknown. Occurrence: Very rare. Low priority for conservation action. Published as part of Bariche, Michel & Fricke, Ronald, 2020, The marine ichthyofauna of Lebanon: an annotated checklist, history, biogeography, and conservation status, pp. 1-157 in Zootaxa 4775 (1) on pages 77-78, DOI:10.11646/zootaxa.4775.1.1, http://zenodo.org/record/3983887